PENGEMBANGAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN USAP ABUR DI TK SUTITAH SOEDARSO 1 KECAMATAN JONGKAT - Yunita Sri Widarti; Muhammad Ali; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractMotor skills of children in kindergarden are emphasized on the coordination of fine motor movements in this case related to placing or holding an object using the fingers. This study aims to describe the development of fine motor skills of children aged 5-6 years through rubbing activities at Sutitah Soedarso Kindergarten 1. The research method used is descriptive method with qualitative research the subject in the study were teachers and children aged 5-6 years. The research location is in Sutitah Sedarso 1 Kindergarten, especially in group B1 class. Data collection techniques used in this study were participant observation, interviews and documentation. The results showed that: the development that the teacher did in developing the fine motor skills of children in learning through this blurry swab activity was that the teacher used the demonstration method so that children more easily understood, imitating what the teacher had exemplified. The teacher also provides a motivational approach to children when doing blurry rubbing activities and asks children to focus on learning and see what the teacher will exemplify. The examples of activities given by the teacher are the teacher giving examples of how to trace the pattern correctly, coloring the edges of the pattern neatly and does not go out of line, and wipe the color blur well so that the resulting color is also good. Then on the child's development that the fine motor development of the child is good after being given a blurry swipe activity in learning, the child is able to coordinate eyes and hands and work well.Keywords: Children Aged 5-6 Years, Fine Motor Development, Gray Swab Activity